Modified iris system: initial experience with a new technology for safety in hiatal surgery in pediatric patients - Joel Cazares; Eduardo De la Rosa-Bustamante; Jorge Colín-Garnica; Arturo Guillen-Cárdenas; Marbella Sepulveda-Valenzuela; Miguel Torres-Salas; Jorge Alberto Cantú-Reyes (Journal of Pediatric Surgery Open)
Purpose: We present our initial experience with a modified IRIS U-kit system (MIUS) (Stryker, USA) for real-time esophageal visualization during Nissen fundoplication (NF) surgery in pediatric patients, aiming to enhance safety and reduce complications, especially in cases involving esophageal dysmotility and neurological impairments. Methods: A retrospective, experimental study from April to June 2023 including patients with Gastroesophageal Reflux Disease (GERD). The IRIS U-kit, originally designed for urology, was adapted to aid esophageal visualization. This system utilized an illuminated ureteral stent with optical fibers inserted into a feeding tube (bougie). Results: Five pediatric patients with an average age of 6.2 years successfully underwent laparoscopic NF. Three patients had neurological impairments, one had trisomy 21, and one had no neurological issues. Using MIUS enabled real-time esophageal visualization throughout the surgery, even in challenging areas affected by periesophagitis. No complications were reported. All NF procedures, with or without additional interventions like gastrostomy and pyloroplasty, were completed safely. Discussion: NF surgery in pediatric patients, especially those with neurological impairments, poses risks of complications including perforations. Real-time esophageal visualization using the MIUS proved valuable in enhancing surgical safety, preventing complications and as an educational tool for resident training. Conclusions: The MIUS demonstrated feasibility and safety in NF surgery for pediatric patients, even in cases with esophageal dysmotility and neurological impairments without using endoscopy. This innovative approach has the potential to be applied in reoperations, Heller myotomies, and esophageal atresias. To our knowledge, this is the first successful use of the IRIS system in non-urological patients.